Potential of Sulforaphane as a Natural Immune System Enhancer: A Review - Castillo-Nara, A; Mahn-Osses, A (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Brassicaceae are an outstanding source of bioactive compounds such as ascorbic acid, polyphenols, essential minerals, isothiocyanates and their precursors, glucosinolates (GSL). Recently, GSL gained great attention because of the health promoting properties of their hydrolysis products: isothiocyanates. Among them, sulforaphane (SFN) became the most attractive one owing to its remarkable health-promoting properties. SFN may prevent different types of cancer and has the ability to improve hypertensive states, to prevent type 2 diabetes–induced cardiomyopathy, and to protect against gastric ulcer. SFN may also help in schizophrenia treatment, and recently it was proposed that SFN has potential to help those who struggle with obesity. The mechanism underlying the health-promoting effect of SFN relates to its indirect action at cellular level by inducing antioxidant and Phase II detoxifying enzymes through the activation of transcription nuclear factor (erythroid-derived 2)-like (Nrf2). The effect of SFN on immune response is generating scientific interest, because of its bioavailability, which is much higher than other phytochemicals, and its capacity to induce Nrf2 target genes. Clinical trials suggest that sulforaphane produces favorable results in cases where pharmaceutical products fail. This article provides a revision about the relationship between sulforaphane and immune response in different diseases. Special attention is given to clinical trials related with immune system disorders. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.